Antioxidant and Tyrosinase Inhibitory Effects of Neolignan Glycosides from Crataegus pinnatifida Seeds - Huang, Xiao-Xiao; Liu, Qing-Bo; Wu, Jie; Yu, Li-Hong; Cong, Qian; Zhang, Yan; Lou, Li-Li; Li, Ling-Zhi; Song, Shao-Jiang (Planta Medica, 2014)
In our efforts to find an inhibitor of melanin formation and develop potential depigmenting agents for skin-protecting cosmetics and medicinal products from natural resources, we focused on the seeds of Crataegus pinnatifida which showed antioxidant and tyrosinase-inhibiting activities. By activity-guided fractionation of an extract of C. pinnatifida seeds, four new neolignan glycosides, pinnatifidaninsides A–D (1–4), along with two known compounds (5–6), were isolated. Their structures were elucidated by spectroscopic analyses, especially 1D, 2D NMR and CD spectra. The antioxidant and tyrosinase-inhibiting activities of all isolates were assayed. Compound 6 showed good activity against 2,2-diphenyl-1-pikrylhydrazyl, while compounds 1, 2, 5, and 6 exhibited strong 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) free radical scavenging activity, being as effective as, or even more effective than the positive control Trolox. Moreover, compounds 5 and 6 displayed a moderate mushroom tyrosinase inhibitory activity.
Keywords: Crataegus pinnatifida; Rosaceae; hawthorn; neolignan glycosides; tyrosinase-inhibiting activity; antioxidant activity